AUGMENTED REALITY BERBASIS PELACAKAN OBJEK PEMBELAJARAN MOTIF DAN MAKNA KAIN TENUN ATAMBUA - Pereira, Yubita Dasilva; Malahina, Edwin Ariesto Umbu (Jurnal Manajamen Informatika Jayakarta, 2025)
This study, titled "Object Tracking Based on Augmented Reality in Interactive Learning for the Recognition of Motifs and Philosophy of Atambua Woven Fabrics," aims to develop an Augmented Reality (AR)-based application capable of tracking objects on woven fabrics and providing interactive information about the motifs and their underlying philosophy. By leveraging AR technology, this application is expected to enhance public understanding, particularly among younger generations, of the cultural values embedded in the woven fabrics of East Nusa Tenggara, specifically in Belu Regency. The research was conducted at the Atambua Weaving Gallery using the Waterfall software development method. The expected outcome of this study is the creation of an interactive tool that can support cultural heritage preservation while increasing the gallery’s appeal to visitors. Thus, this research has the potential to make a significant contribution to cultural preservation efforts and the development of interactive education in Indonesia.